Legal Review of the Procedure for Settling Liwath Crimes in the Context of the Jinayat Procedure Law in Banda Aceh City - Syifaulqolbi Syifaulqolbi; Hasnul Arifin Melayu; Riadhus Sholihin (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2026)
The evidentiary efforts for the criminal offense of Jarimah Liwath in Aceh, regulated in the Qanun Acara Jinayah, are often suboptimal and constrained by the demand for strict standards of evidence. This problem arises in the context of implementing Aceh's special autonomy, which began with Law Number 44 of 1999 concerning the Administration of the Special Region of Aceh Province, was followed by Law Number 18 of 2001 concerning Special Autonomy for Nanggroe Aceh Darussalam Province, and subsequently replaced by Law Number 11 of 2006 concerning the Governance of Aceh. This framework encompasses the implementation of Islamic Sharia Law and Jinayah (Criminal) Law. One of the criminal offenses in the Qanun Jinayah is Jarimah Liwath, the settlement procedure of which is regulated in the Qanun Acara Jinayat (Code of Criminal Procedure). This research aims to conduct a juridical review of the Jarimah Liwath settlement procedure (including evidentiary efforts) within the context of the Qanun Acara Jinayat in Banda Aceh City, as well as to identify the constraints faced by law enforcement officials, particularly the Satpol PP and WH. The methodology employed is a normative-empirical approach using qualitative descriptive techniques, through interviews and documentation. The research findings indicate that evidentiary efforts for Jarimah Liwath by investigators have not been optimal. This is due to the difficult nature of proving Jarimah Liwath, where the Qanun Acara Jinayat mandates strict standards of evidence. Juridically, a review of the implementation of these rigorous evidentiary procedures is necessary for the settlement of Jarimah Liwath cases.